SP0032 The contribution of physiotherapists to early detection of inflammatory arthritis. (15th June 2017) - Kirwan, P
Abstract : Early recognition of inflammatory arthritis is of utmost importance, as failure to do so can delay appropriate treatment and result in permanent joint damage and disability. This presentation will set out to explore the role a Physiotherapist/Healthcare Professional can play in recognition of inflammatory joint disease. Healthcare Professionals/Physiotherapists are often the first point of contact for patients suffering from joint/musculoskeletal pain. They are therefore very well positioned to be the first to identify possible inflammatory sources of pain versus non-inflammatory sources. Useful clinical tools which aid in this decision making process will be discussed. The question as to whether a physiotherapist can recognise inflammatory joint disease versus non-inflammatory joint conditions will be explored with the aim being to highlight the important role a physiotherapist can play in this important diagnostic challenge. With reference to ongoing clinical and research work in this field, this presentation will set out to ask whether or not a Healthcare Professional/Physiotherapist can accurately recognise/diagnose inflammatory arthritis and whether they miss inflammatory arthritis. Disclosure of Interest: None declared